Perancangan Sistem Kotak Ide Digital sebagai Pengelolaan Inovasi Berbasis Website pada Bappelitbang Sumatera Utara - Adam Haris; Fauzi Syahputra Harahap; Imam Adlin Sinaga (Pusat Riset dan Inovasi Nasional, 2026)
The development of community driven innovation plays an important role in supporting regional growth. However, the idea management process at Bappelitbang North Sumatra, which is still carried out manually, often results in inefficiencies in verification, evaluation, and idea tracking. This study aims to design and develop a web-based Digital Idea Box Information System as a solution to simplify the submission and management of community innovations. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, which includes requirement analysis, system design using UML, implementation with PHP and MySQL, and system testing. The testing phase employed the black-box testing method to ensure that all system functions operated according to the specified requirements. The results show that the system successfully provides key features such as user registration, idea submission, status monitoring, admin verification, and report generation. Based on the test results, all features functioned properly without significant errors. Overall, this system improves the effectiveness, transparency, and speed of innovation management at Bappelitbang North Sumatra. In addition, it offers a more accessible platform for the public to share their creative ideas in an organized and convenient manner.